2015
DOI: 10.1080/2374068x.2015.1133789
|View full text |Cite
|
Sign up to set email alerts
|

Effect of shielding gas on the properties and microstructure of melted steel surface using a TIG torch

Abstract: This version is available at https://strathprints.strath.ac.uk/49507/ Strathprints is designed to allow users to access the research output of the University of Strathclyde. Unless otherwise explicitly stated on the manuscript, Copyright © and Moral Rights for the papers on this site are retained by the individual authors and/or other copyright owners. Please check the manuscript for details of any other licences that may have been applied. You may not engage in further distribution of the material for any pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 16 publications
(14 reference statements)
2
20
0
Order By: Relevance
“…However, in the present work, substantial increases in the microhardness were recorded. Initially, this result was not entirely unexpected, as previous work with lasers and TIG employing higher energy inputs than the present work but with similar volumes of SiC powder, reported SiC particles along with iron silicides, contributing to an increased hardness [26,[28][29][30][31].…”
Section: Energy Kvsupporting
confidence: 79%
See 1 more Smart Citation
“…However, in the present work, substantial increases in the microhardness were recorded. Initially, this result was not entirely unexpected, as previous work with lasers and TIG employing higher energy inputs than the present work but with similar volumes of SiC powder, reported SiC particles along with iron silicides, contributing to an increased hardness [26,[28][29][30][31].…”
Section: Energy Kvsupporting
confidence: 79%
“…A modified surface of hardness >1000Hv to a depth ≥1.4mm was developed. This study was expanded by Muñoz-Escalona et al [31], who found that substituting helium for argon as the shielding gas in single track TIG processing, reduced the melt zone hardness due to the significantly higher temperatures recorded in the parent microalloyed (MA) steel. Changes in heat input, shielding gas, and alloying powder composition, volume fraction and size, can also influence the surface roughness.…”
Section: Introductionmentioning
confidence: 99%
“…3, in general there are higher values of temperature registered at the end of the melted track, where an average increase of ~50C was obtained between the start and the end of the melted track. This small increase is associated to a pre-heat process [18][19]. As observed, the temperature increased when SiC particles were incorporated.…”
Section: Resultsmentioning
confidence: 51%
“…In a study by Patel et al [18], ~5µm SiC was dissolved into a microalloyed steel using a TIG torch, with argon as the shielding gas, to produce a modified surface of hardness >1000Hv to a depth ≥1.4mm. Muñoz-Escalona et al [19], found that substituting helium for argon as the shielding gas in single track TIG processing, reduced hardness, due to the significantly higher temperatures recorded in the parent steel. Changes in heat input, shielding gas, and alloying powder composition, volume fraction and size, can also influence the surface roughness.…”
Section: Introductionmentioning
confidence: 99%
“…Both techniques require a gaseous shielding atmosphere, usually 2, Ar, He, CO2 or mixture of these gases. The shielding gas protects the metal transfer stream and the molten weld pool from contamination resulting from dissolution from the atmosphere of nitrogen, oxygen and water vapour , which often have a deleterious effect on the mechanical properties of the modified surface ] [13][14][15][16][17]. Shielding gases also provide a medium for the electrical current to flow in the plasma jet between workpiece and electrode.…”
Section: Introductionmentioning
confidence: 99%